Inhibition of return emerges with non-predictive spatial cueing of the stop-signal - Haque, Md. Tanbeer; Conci, Luca; Bardella, Giampiero; Fagioli, Sabrina; Ferraina, Stefano; Di Bello, Fabio; Pani, Pierpaolo (Frontiers in Human Neuroscience, 2025)
The ability to suppress an inappropriate response can be influenced by several factors, including providing information on where to pay attention. For example, the spatial prediction of the stop signal location enhances inhibitory control in a Stop Signal Task. Here, we test whether a non-predictive spatial cueing improves inhibitory control as well. In this experiment, participants observed a vertical bar moving from a central position toward one of two circles on the screen. They were asked to press a key when the bar's motion was interrupted (go signal). In 25% of the trials (stop signal trials), after a variable delay following the go signal, a visual target (stop signal) appeared in one of the circles, requiring participants to inhibit their response to the go signal. In half of these trials, the stop signal appeared on the same side as the go signal (valid condition), and in the other half, it appeared on the opposite side (invalid condition). Our results show a facilitation effect for stop trials in the invalid condition compared to the valid condition, for targets occurring from 300 ms onward the go signal. This suggests an involvement of Inhibition of Return (IOR) in affecting the stop signal detection during motor control. Our findings provide new insights into the interaction between attentional processes and motor control, highlighting a temporally focused influence of exogenous attention in shaping motor inhibition.